The role of knowledge networks in the transformation of the teaching and learning process at the Normal School - Cañón Núñez, Patrick Yovany; García, Hasly Yanneth (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2022)
Objective: to make visible the transformations in the teaching and learning process aroused from the implementation of knowledge networks between teachers and students at the I.E.D Higher Normal School María Auxiliadora in Villapinzón. Originality/contribution: The innovative contribution lies in the evidence that knowledge networks are a beneficial pedagogical strategy for the educational community, it articulates alternatives for the implementation of ICT and proposes a hybridization for the implementation of these tools in education. Method: it is based on the interpretive paradigm through a permanent and self-reflective reading of reality by means of the qualitative approach. The action research method is used to approach the collection of information. 457 actors of the educational community participated and supported the implementation of knowledge networks at Normal School. Information strategy/data collection: surveys, forms and photographs were used to collect points of view, needs and reflections about the effects of the pandemic on teaching and learning activities. Findings are analyzed from the reflection and rethinking of practices. Conclusions: The need for a meta education based on flexibility, criticality, autonomy, and self-regulation, together with the social contextualization of the individual.